Determinants of and Prospects for Market Access in Frontier Economies - Hugo C. Alexandrino da Silva, Victor (IMF Working Papers; Working Paper ;, 2021)
In recent years, we have observed an increase in low-income countries' (LICs) access to international capital markets, especially after the Global Financial Crisis (GFC). This paper investigates what factors-country-specific macroeconomic fundamentals and/or external variables-have contributed to the surge in external bond issuance by these LICs, which we refer to in our paper as 'frontier economies'. Using data on public and publicly guaranteed (PPG) external bond issuance, outstanding PPG bond stock, as well as sovereign spreads, we employ panel data analysis to examine factors related to the increase in issuance by these economies as well as the reduction in their spreads over time. Our empirical study shows that both country-specific fundamentals (such as public debt, current account balance, level of reserves, quality of institutions) and external variables (such as US growth and the VIX index) play a role in explaining the increased amount of issuance and the decline in spreads of frontier economies' sovereign bonds. The impact of some of these variables on issuance appears to reflect a country's need to issue bonds for external financing ('the supply side' of bond issuance), while others appear to correlate more through their impact on investors' appetite for a country's debt ('the demand side'). In addition, the impact of country-specific variables can also be affected by external factors such as global risk appetite. Our analysis of key factors that have contributed to increased market access for frontier economies over the past decade provides important information to gauge the prospects for their continued market access, and for other LICs to join this group by tapping international markets for the first time.